Discussion on Some Typical Phenomena during Unsteady Casting Process. Issue 7 (4th May 2016) - Li, Linping; Wang, Xinhua; Deng, Xiaoxuan; Suo, Jinliang; Ji, Chenxi
Abstract : To the authors' best knowledge, unsteady period casting is detrimental for the sound casting and good quality. On the basis of mathematical model and experimental observation, some typical unsteady phenomena including breakout shell, unsteady solidification, level hunching, and steel cleanliness are discussed presently. The results show that solidification factor in the mold is within 22–28 mm min −1/2 and the superheat carried by the impinging flow, about 300 mm below the meniscus, is enough to remelt the thin solidified shell of narrow face. After the analysis of unsteady crater end transition mechanism, mathematical model verified by pin shooting is established and the expression for predicting the actual unsteady length is derived. There is also a typical mold level hunching occurring during the ladle change period of high‐speed casting, which cannot be elucidated by unsteady bulging due to the aperiodic profile. Therefore, the clog–unclog mechanism is proposed. With respect to the cleanliness, powder entrapment occurs during the first two slabs of casting start, ladle change, SEN change, casting end period and the reoxidation is dominant in the casting start. Finally, the quality of cold‐rolled coils is improved by the optimization of speed transition route in the casting start. Abstract : In this work, based on the mathematical and experimental results, the unsteady state process is incorporated into four categories, including breakout shell investigation, crater end tracking, mold level hunching, and steel cleanliness evaluation, respectively. As a result, the contour of breakout shell thickness, expression of the actual unsteady length, mechanism of mold level hunching, and optimization of speed transition route are proposed finally.